Survival after local anaesthetic overdose : a comparison of the success of resuscitation after established cardiotoxicity caused by ropivacaine or bupivacaine - Whitehead, Paul Neville (Department of Anaesthesia, 2017)
The purpose of this thesis is to review the pharmacology and toxicity of local anaesthetics, particularly highlighting the differences between bupivacaine and ropivacaine and to present an experiment attempting to establish whether ropivacaine is a safer drug, once cardiotoxicity has occurred.